Effects of Frequency and Duration of Interrupting Sitting on Cardiometabolic Risk Markers - Maylor, Benjamin D.; Zakrzewski-Fruer, Julia K.; Stensel, David J.; Orton, Charlie J.; Bailey, Daniel P. (International Journal of Sports Medicine, 2019)
Interrupting prolonged sitting with short multiple bouts of moderate-intensity physical activity (PA) can improve postprandial cardiometabolic risk markers. This study examined the effect of high and low frequency PA bouts (matched for total PA duration and energy expenditure) on postprandial cardiometabolic responses when compared with prolonged sitting. In this three-condition randomised crossover trial, 14 sedentary, inactive females (33.8±13.4 years, BMI 27.1±6.3 kg/m2) completed 3, 7.5 h conditions: 1) prolonged sitting (SIT), 2) high-frequency PA breaks (HIGH-FREQ) consisting of 15 ×2 min bouts of moderate-intensity treadmill PA every 30 min, and 3) low-frequency PA breaks (LOW-FREQ) consisting of 3 ×10 min bouts of moderate-intensity treadmill PA every 180 min. The PA bouts were performed at 65% of peak oxygen uptake. Net incremental area under the curve (iAUC) for each 7.5 h condition was calculated for glucose, insulin and triacylglycerol (TAG) concentrations. Insulin iAUC was significantly (p<0.026) lower during HIGH-FREQ (mean [95%CI]; 82.86 [55.02, 110.70] µU/mL∙7.5 h) than LOW-FREQ (116.61 [88.50, 144.73] µU/mL∙7.5 h) and SIT (119.98 [92.42, 147.53] µU/mL∙7.5 h). Glucose and TAG iAUC did not differ between conditions. Engaging in higher-frequency PA breaks may be effective in attenuating postprandial insulin responses compared with lower-frequency PA breaks and prolonged sitting.
Keywords: physical activity; sedentary behaviour; glycaemia; lipids; activity breaks